2022
DOI: 10.1097/dss.0000000000003645
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology Match Preference Signaling Tokens: Impact and Implications

Abstract: BACKGROUNDThe dermatology residency application process implemented a new system of preference signaling tokens (PSTs) in the 2021-2022 cycle to allow applicants to express a higher level of interest in specific programs. Limited data are available on the utilization and impact of these tokens.OBJECTIVETo determine the impact of PSTs on the application process and where in the process PSTs had the greatest influence.MATERIALS AND METHODSA 14-question survey was sent to 62 ACGME-accredited dermatology residency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“… 7 The rate at which applicants received interview offers was significantly higher for programs they signaled compared to nonsignaled programs in the otolaryngology, dermatology, and urology residency match. 7 15 16 These specialties reported that signals were most commonly used as part of the initial application review to extend interviews and as a tiebreaker for similar applications, but not for determining a rank list, which is consistent with our findings. 7 Additionally, orthopaedic PDs surveyed ranked signaling only below away rotation performance and personal knowledge of the applicant in terms of importance for residency selection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 7 The rate at which applicants received interview offers was significantly higher for programs they signaled compared to nonsignaled programs in the otolaryngology, dermatology, and urology residency match. 7 15 16 These specialties reported that signals were most commonly used as part of the initial application review to extend interviews and as a tiebreaker for similar applications, but not for determining a rank list, which is consistent with our findings. 7 Additionally, orthopaedic PDs surveyed ranked signaling only below away rotation performance and personal knowledge of the applicant in terms of importance for residency selection.…”
Section: Discussionsupporting
confidence: 89%
“… 7 8 11 13 14 Survey studies in dermatology, otolaryngology, and urology have found considerable advantages to using signaling such as improving the distribution of interview offers among applicants and allowing seriously interested applicants to standout to desired programs. 7 15 16 PDs in otolaryngology reported that signals were used as a tiebreaker for similar applications and as part of the initial application review algorithm. 7 The rate at which applicants received interview offers was significantly higher for programs they signaled compared to nonsignaled programs in the otolaryngology, dermatology, and urology residency match.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 These opinions are consistent with findings from postmatch analysis of dermatology and ENT data, which both demonstrated a markedly increased likelihood of receiving an interview at a 'signaled' program compared with programs that did not receive a 'signal' designation. 13,16 This notable effect was experienced by applicants across all quartiles of competitiveness, 13 consistent with 61.3% of our PD respondents thinking that the PSP would improve the interview rates of midtier to-low-tier applicants.…”
Section: Discussionsupporting
confidence: 78%
“…Compared with the 30 signaling tokens allotted to orthopaedic surgery applicants for the 2022 to 2023 match, otolaryngology, urology, dermatology, internal medicine, and general surgery allotted between 3 and 5 tokens for each applicant to preserve the value and intent associated with the 'signal' designation. [10][11][12][13][16][17][18] The broad variation alludes to the uncertainty surrounding the optimal token allotment that would maximize the discrete value while minimizing the likelihood of 'nonsignalers' being perceived as disinterested. The second otolaryngology match using preference signaling allotted four tokens per candidate, a decrease from five tokens during their inceptive cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation